2018
DOI: 10.3389/fmicb.2018.00487
|View full text |Cite
|
Sign up to set email alerts
|

Host and Aquatic Environment Shape the Amphibian Skin Microbiome but Effects on Downstream Resistance to the Pathogen Batrachochytrium dendrobatidis Are Variable

Abstract: Symbiotic microbial communities play key roles in the health and development of their multicellular hosts. Understanding why microbial communities vary among different host species or individuals is an important step toward understanding the diversity and function of the microbiome. The amphibian skin microbiome may affect resistance to the fungal pathogen Batrachochytrium dendrobatidis (Bd). Still, the factors that determine the diversity and composition of the amphibian skin microbiome, and therefore may ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 55 publications
4
88
2
Order By: Relevance
“…Jani & Briggs, ; Mshelia et al, ). Host characteristics such as sex, body condition and the presence or absence of pathogens are recognized as important for shaping microbial communities (Britton & Young, ; Cheng et al, ; Ganz et al, ; Hooper, Littman, & Macpherson, ; Jani & Briggs, , ; McKenney et al, ; Mshelia et al, ; NĂ€pflin & Schmid‐Hempel, ). For example, horses in poor body condition have greater microbial diversity and a different suite of microbial species present compared to horses in good body condition (Mshelia et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jani & Briggs, ; Mshelia et al, ). Host characteristics such as sex, body condition and the presence or absence of pathogens are recognized as important for shaping microbial communities (Britton & Young, ; Cheng et al, ; Ganz et al, ; Hooper, Littman, & Macpherson, ; Jani & Briggs, , ; McKenney et al, ; Mshelia et al, ; NĂ€pflin & Schmid‐Hempel, ). For example, horses in poor body condition have greater microbial diversity and a different suite of microbial species present compared to horses in good body condition (Mshelia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, horses in poor body condition have greater microbial diversity and a different suite of microbial species present compared to horses in good body condition (Mshelia et al, ). High loads of the pathogen Batrachochytrium dendrobatidis can not only increase amphibian skin microbial diversity but also alter microbial composition (Jani & Briggs, , ). Microbial community structure is also likely to be shaped by dispersal or transmission as physical distance between hosts can produce barriers to gut microbe transmission that accelerate compositional divergence (Moeller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Important to reintroduction efforts is the observation that different frog species show varying degrees of susceptibility to chytridiomycosis (Fisher et al 2009). Sierra Nevada yellow-legged frogs are one of the most well-studied systems to give insight into chytridiomycosis progression and the role of the host microbiome on disease outcome in the wild (Jani and Briggs 2018). This variation has recently also been shown to exist across populations of R. sierrae (Joseph and Knapp 2018).…”
Section: Implications For Managementmentioning
confidence: 99%
“…Eventually, this detrimental Bd strain made its way into one of the most remote environments of North America, the Dusy Basin within Kings Canyon National Park (Olson et al 2013). The population decline due to Bd spanned two full years before all adult individuals disappeared with relatively high infection intensity and load (Jani 2014, Jani andBriggs 2018). One such local extirpation occurred within Dusy Basin where we had been monitoring R. sierrae populations since 1997.…”
Section: Introductionmentioning
confidence: 99%
“…The amphibian skin microbiome has been proposed as a potential protective factor against chytridiomycosis (Harris et al, ; Becker & Harris, ). While studies have found a clear association between the composition of the amphibian microbiome and population‐level outcomes of Bd invasion (Jani et al, ; Bates et al, ), the demonstrable effect of the amphibian skin microbiome as a protective mechanism against Bd infection has been variable (Harris et al, ; Woodhams et al, ; Jani & Briggs, ). Field and laboratory results suggest that the magnitude of the Bd effect on microbiome can be greater than the magnitude of the microbiome effect on Bd (if any) (Jani & Briggs, ,, ).…”
Section: Introductionmentioning
confidence: 99%